Weight-based discrimination and cortisol output: A systematic review - Maria A. Kalantzis; Daniel M. Maitland; Miranda Yannon; Christina Gaggiano; Jinbo He; Aldo Barrita; Lorelai Symmes; William H. O'Brien (Comprehensive Psychoneuroendocrinology)
Discrimination based on weight status (or weight-related discrimination/stigma) may be related to greater physical and mental health concerns via physiological and psychological phenotypes of stress. Cortisol output, a biomarker of stress, has been measured in relation to weight stigma and weight-related discrimination. This systematic review aims to synthesize existing research on the relationship between weight-related discrimination and cortisol output, evaluate methodological approaches for measuring these constructs, and identify research gaps regarding contextual factors influencing this relationship. A comprehensive search was conducted across multiple databases (PsycINFO, Scopus, ProQuest, and PubMed) from February 1 to July 1, 2024, resulting in 11 eligible studies that examined weight discrimination in relation to cortisol levels. Studies were assessed for quality using the NHLBI Study Quality Assessment Tool, and inter-rater reliability for coding was established at 90 %. The findings revealed a range of sample sizes (45–4341) and diverse participant characteristics, including variations in age, race, and body mass index (BMI). About half (N = 5) of the included studies reported a positive relation between weight stigma and cortisol output. The review also uncovered significant limitations in current methodologies, particularly concerning contextual factors and other marginalized identities, such as socioeconomic status and food insecurity, along with measuring other forms of discrimination in tandem with weight stigma, such as racial discrimination. These findings underscore the need for future research to adopt a more intersectional approach in examining the multifaceted nature of weight stigma and how it relates to a greater stress response in multiple marginalized identities, as well as including longitudinal modeling of weight stigma's impact on biomarkers for stress.